Advances in the management of TTP. (September 2022) - Subhan, M.; Scully, M.
Abstract: Thrombotic thrombocytopenic purpura is an acute life-threatening disorder, associated with a mortality of 90% if unrecognised and untreated. The hallmark is thrombocytopenia and microangiopathic hemolytic anemia, with a blood film characterised by fragmented red cells and end organ damage. The mainstay of treatment is ADAMTS13 replacement, currently with plasma exchange (PEX) and immunosuppression. High dose steroids are used from presentation and anti-CD20 monoclonal antibody therapy, specifically rituximab, is initiated early in the acute disease pathway. The use of the nanobody caplacizumab on confirmation of TTP, by severe ADAMTS13 deficiency (<10iu/dL), has revolutionised acute patient care. Caplacizumab binds the A1 domain, the site on VWF normally occupied by platelets. This results in a quicker normalisation of the platelet count, prevention of exacerbations and refractory disease, reduced PEX and inpatient stay. There is a significant risk of relapse and monitoring of patients allows prophylactic rituximab to be given to prevent further acute admissions.